" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
4x^2+9-12x-(x^2+9+6x)-3x-18=0
-18x-18=0
x=-18/18=-1
(x+4)³+3x=x³+8x+21+12x²
(x+4)^2.(x+4)+3x-x^3-8x-12x^2-21=0
(x^2+16+8x)(x+4)-5x-x^3-12x^2-21=0
x^3+4x^2+16x+64+8x^2+32x-5x-x^3-12x^2-21=0
43x+43=0 x=-1
3(x+3/4)-1/2(x+1/3)=5/12 multiplicamos por 12
36(4x+3/4)-6(3x+1/3)=5
9(4x+3)-2(3x+1)=5
36x+27-6x-2-5=0
30x+20=0 x=-2/3
1/2(x+3)=3/4(2x+8)-1/4
2x+6=6x+24-1
6x+24-1-6-2x=0
4x+17=0 x=-17/4
4x²-12x+9-x²-6x-9-3x²=18
-18x = 18
x=18/-18
x=-1